PENGARUH STORE ATMOSPHERE, CONSUMER INNOVATIVENESS, DAN BRAND IMAGE TERHADAP CONSUMER REPURCHASE INTENTION PADA MCDONALD’S AHMAD YANI PADANG - Fikriando, Eko; Syafrizal, Syafrizal (Menara Ilmu, 2020)
This research was conducted to study the factors that influence the influence of brand image store atmosphere and consumer innovation on consumer repurchase intentions on Ahmad Yani McDonald's. The independent variables in this study are store atmosphere, brand image, and consumer innovation, while consumer repurchase intentions are used as the dependent variable. The sampling technique was done by purposive sampling so that 170 respondents were obtained as research samples. The data analysis technique used in this study is multiple linear regression, where the results obtained are store atmosphere, brand image and consumer innovation have a significant influence and positive value. Keywords :hedging, instrument derivatives, financial distress, liquidity ratio, size